Mechanisms of the Early Fatigue Damage in Metallic Materials - Jaroslav Polak; Jiri Man; Martin Petrenec (Communications - Scientific letters of the University of Zilina, 2006)
The early stages of the fatigue damage in f.c.c. and b.c.c. metals are studied using high resolution techniques. The localization of the cyclic plastic strain results in formation persistent slip bands (PSBs) with specific dislocation structure. Characteristic surface relief is formed at locations where PSBs emerge on the surface. It consists of extrusions and intrusions separated by the original flat surface. Atomic force microscopy is used to study the details of the surface relief. The experimental findings are discussed in terms of the point defect model of fatigue crack initiation.